(untitled) (Environment & Health, 2015)
The Objective. To consider a second laws of thermodynamics to assessing the body’s resistance to adverse influences. To substantiate the health entity and its operational definition. To create a simple diagnostic assessment system of health level. Material and methods. In the multi-year studies there was defined the interconnection of the health with the clinical-physiological indicators of thousands healthy and sick people, were also defined manifestations and prevalence of risk factors for non-communicable diseases. Results. On the base of indirect determination of the maximum capacity of aerobic energy production, there was developed the methodology and simple method of somatic health diagnostic. There was proven the interconnection between the level of health and the risk factors for non-comunicable diseases and also their prevalence. We described the phenomena of "safe level of health" and "self-development" of pathological process when a person comes from a health "safe zone".